Viaţa la noi - Larcher, Jonathan (France, 2010)
In Romania, north of Bucharest, the Gypsy families of a small villabe are gathering for an Easter celebration. The filmmaker is accompanying them in an attempt to record their ceremonies, but soon comes to realize that he cannot ever view the proceedings with an insider's lens - only the Roma can do that.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films